FACTORS AFFECTING ORGANIZATIONAL COMMITMENT (A HUMAN RESOURCE MANAGEMENT LITERATURE STUDY) - Wydyanto, Wydyanto; Yandi, Andri (Dinasti Publisher, 2020)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence organizational commitment, namely: Individual Characteristics, Compensation, and Job Satisfaction, A Study of Human Resource Management Literature. The results of this research library are that: 1) individual characteristics have an effect on job satisfaction; 2) compensation affects job satisfaction; 3) individual characteristics affect organizational commitment; 4) compensation affects organizational commitment; and 5) job satisfaction affects organizational commitment.